Analyzing the impact of Gender Inequality on Economic Development in Pakistan: ARDL Bound Test Cointegration Analysis - Khurshid, Nabila; Fiaz, Asma; Khurshid, Jamila (International Journal of Economics and Financial Issues, 2020)
This research explores the issue of gender discrimination and offers its solutions with reference to Pakistani context. A time series data from the period of 1990 to 2016 was used in this study. Dependent variable is GDP growth rate whereas independent variables are gender inequality index (GII), Term of Trade (TOT), Literacy rate (Lit), Interest Rate (CMR), Inflation (wpi) and Female access to Higher Education (HE). For time series we check stationarity of data by employing Unit Root Test which showed that series have mixed level interrogation, so, ARDL technique for best possible estimation. This has highlighted the long run relationship between inequality and economic growth in Pakistan. The results indicate that gender inequality and economic growth are inversely related to each other. Further results revealed that Literacy rates, Interest rate and inflation rate are negatively and significantly related to economic development while female access to higher education was found to have positive and significant impact while terms of trade have negative and insignificant impact on economic development. Keywords: Economic Development, Gender Inequality, Gender Inequality Index, Pakistan JEL Classifications: O1, O2, O4, O5 DOI: https://doi.org/10.32479/ijefi.10028